MERANCANG TEKNIK PENILAIAN BERBASIS KELAS: Kasus Guru Fiqih Tsanawiyah - Asis Saepuddin (Jurnal Pendidikan Islam, 2012)
Previously, the teachers of fiqh at Madrasah Tsanawiyah still have the difficulties in correctly measuring the competence and student learning outcomes. It means, the validity of the result of teacher assessments is still in doubt. It’s caused the lack of knowledge and variation in assessing their learning outcomes. The teacher of Madrasah Tsanawiyah on average are not familiar with classroom-based assessment techniques that have not mastered the basic techniques required in the assessment of classroom-based assessment techniques, such as product assessment, portfolio, project, performance, attitude and personal assessment. This paper aims to introduce a class-based assessment techniques and then describe of fiqh teacher competency in designing classroom-based assessment techniques. This research uses qualitative-descriptive method, where instruments for data collection are observation/observation sheets and test. The results of data processing indicates that after receiving the learning materials about classroom assessment techniques, which include product assessment techniques, portfolios, projects, performance, attitude and self-assessment, the competence of fiqh teachers in designing classroom-based assessment techniques is considered at the average level.